INTELLIGENT FIRE PROTECTION SYSTEM FOR MINI APARTMENT BUILDINGS WITH REMOTE MONITORING AND CONTROL - Nguyen, Le-Minh-Quan; Dang, Tran-Gia-Bao; Vo, Binh-An; Hong, Vi-Cuong; Truong, Tuan-Minh; Le, Dinh-Duc-Vinh; Dang, Phuc-Khanh; Nguyen, Quoc-Bao; Le, Xuan-Cuong; Nguyen, Binh-Hau; Nguyen, Thi-Ngoc-Thao; Nguyen, Van-Hai; Nguyen, Huynh-The-Hung; Nguyen, Anh-Tuan; Le, Hoang-Nhat-Huy; Nguyen, Van-Hiep (Indonesian Journal of Engineering and Science, 2026)
This study presents an integrated fire protection system for space-constrained residential buildings using a Mitsubishi PLC, variable frequency drive, cascade PID control, HMI/SCADA, and an ESP32-based IoT gateway. The system is designed to regulate pipeline pressure and water level during firefighting while enabling local and remote supervision. Experimental validation on an IT-5200 didactic platform shows that the uncontrolled system requires about 42 s to reach the reference level and exhibits significant overshoot. After implementing the cascade strategy with an outer PID level loop and an inner PI pressure loop, the settling time decreases to about 16 s, with negligible overshoot, minimal steady-state error, and improved disturbance rejection. The developed HMI/SCADA supports role-based access, alarm handling, and parameter setting, while the IoT layer enables web monitoring and SMS alerts. The proposed architecture offers a practical and scalable solution for reliable fire protection in cost- and space-constrained building environments.